The importance of horizontal and vertical take-off velocity for elite female long jumpers - Letzelter, S. (New Studies in Athletics, 2011)
Although biomechanical research on elite long jumpers has increased knowledge about the event, the analyses conducted to date suffer from certain limitations, including small sample sizes and few studies on women. Among issues that are still open are the statistical reliability of findings about the horizontal and vertical components of take-off velocity and whether findings are equally valid for men and women.